2018
DOI: 10.2147/ndt.s148248
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction of cortical synapse-specific mitochondria in developing rats exposed to lead and its amelioration by ascorbate supplementation

Abstract: BackgroundLead (Pb) is a widespread environmental neurotoxin and its exposure even in minute quantities can lead to compromised neuronal functions. A developing brain is particularly vulnerable to Pb mediated toxicity and early-life exposure leads to permanent alterations in brain development and neuronal signaling and plasticity, culminating into cognitive and behavioral dysfunctions and elevated risk of neuropsychiatric disorders later in life. Nevertheless, the underlying biochemical mechanisms have not bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…Moreover, in support of previous studies in human subjects,1,6,8,17,32,84,85 our results suggest that blood Pb levels serve as a valuable diagnostic measure of Pb-mediated dysregulation of neurological functions. In addition, while our study implicates alterations in synapse-specific protein translation as a potential mechanism underlying Pb-induced alterations in synapse maintenance, plasticity; and consequently on memory and cognition as well as vulnerability to psychological stress, it also establishes ascorbic acid as an important therapeutic agent against Pb neurotoxicity,44,45,47,48 The mechanism of ascorbate-mediated neuroprotection in Pb toxicity seems to be multifactorial, stemming from both its antioxidant properties and its Pb chelating function. Being a lactone containing an enediol group, ascorbate can form a soluble complex with Pb, enhancing its urinary excretion while also preventing its gastrointestinal absorption, and eventually lowering its blood levels and reducing its bioavailability 70,86,87…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Moreover, in support of previous studies in human subjects,1,6,8,17,32,84,85 our results suggest that blood Pb levels serve as a valuable diagnostic measure of Pb-mediated dysregulation of neurological functions. In addition, while our study implicates alterations in synapse-specific protein translation as a potential mechanism underlying Pb-induced alterations in synapse maintenance, plasticity; and consequently on memory and cognition as well as vulnerability to psychological stress, it also establishes ascorbic acid as an important therapeutic agent against Pb neurotoxicity,44,45,47,48 The mechanism of ascorbate-mediated neuroprotection in Pb toxicity seems to be multifactorial, stemming from both its antioxidant properties and its Pb chelating function. Being a lactone containing an enediol group, ascorbate can form a soluble complex with Pb, enhancing its urinary excretion while also preventing its gastrointestinal absorption, and eventually lowering its blood levels and reducing its bioavailability 70,86,87…”
Section: Discussionmentioning
confidence: 79%
“…In particular, therapeutic effects of ascorbate in the events of Pb exposure and toxicity have been well-documented by a number of groups 42–47. Of note, our recent study has shown appreciable recovery of early life Pb-induced synapse-specific mitochondrial bioenergetic defects by ascorbate supplementation 48…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Pb also disrupts developmental cortical plasticity, causing dysfunction in neurodevelopment [25]. Moreover, prenatal exposure to Pb affects the activity and expression of key synaptic proteins [10], impairs the functioning of synaptic mitochondria [7,42], disrupts the energy metabolism of neurons and astrocytes, and leads to impaired metabolic cooperation between these cells [43].…”
Section: Introductionmentioning
confidence: 99%
“…Our own studies have provided evidence for the amelioration of early-life (perinatal and postnatal—from gestational day (GD) 15 to postnatal day (PND) 21) Pb-mediated effects on the nerve terminals of multiple brain regions, such as cerebral [ 293 ], hippocampal [ 293 ], and cerebellar synapses [ 294 ], by maternal AA supplementation. In particular, we observed a marked reversal of Pb-mediated alterations in synaptic bioenergetics with the rescue of defects in the mitochondrial membrane potential (MMP) and activities of the enzymes of the electron transport chain (ETC) [ 294 , 295 ]. Improvements in endogenous antioxidant pathways (particularly glutathione signaling) concomitantly with reduced oxidative damage to proteins and lipids were also observed in our model of AA supplementation in rats developmentally exposed to Pb [ 294 , 295 ].…”
Section: Aa As a Potential Ameliorative Agent In Pb Neurotoxicitymentioning
confidence: 99%